FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PREEKLAMSIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS MARAWOLA - Indah Sari, Andi Nur; Nuraliah; Safira (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2024)
Preeclampsia is a potentially dangerous pregnancy complication characterized by high blood pressure. Based on the results of researchers' interviews with 5 pregnant women who visited the Marawola Community Health Center, 3 of them said that they were experiencing their first pregnancy, and usually felt dizzy and their blood pressure was higher than before pregnancy. The aim of this research is to determine the factors associated with preeclampsia in pregnant women in the Marawola Community Health Center working area. This type of research is analytical with a cross sectional approach. Data types use primary data and secondary data. The sampling technique uses random sampling. Data analysis used univariate and bivariate analysis. The population in this study was all 125 pregnant women in the Marawola Community Health Center working area. The sample in this study consisted of 33 respondents. The results of this study show that there is a significant relationship between maternal age with p value = 0.000, gravida p value = 0.005 and maternal BMI p value = 0.008 with the incidence of preeclampsia in the Marawola Health Center working area. The conclusion is that there is a relationship between BMI, gravida and age and preeclampsia in pregnant women. Suggestions: It is hoped that this research can become a reference in libraries in developing knowledge about nursing. Pregnant women are expected to pay attention to their health conditions, especially blood pressure during pregnancy and pay attention to the risks that occur during pregnancy, apply the use of contraception for mothers who are more than 40 years old and Avoid pregnancy at a young age because it will endanger the mother and child.